The Fraction of Rhinovirus Detections Attributable to Mild and Severe Respiratory Illness in a Setting of High Human Immunodeficiency Virus Prevalence, South Africa, 2013–2015. (22nd December 2018) - Hellferscee, Orienka; Treurnicht, Florette K; Walaza, Sibongile; Du Plessis, Mignon; Von Gottberg, Anne; Wolter, Nicole; Moyes, Jocelyn; Dawood, Halima; Variava, Ebrahim; Pretorius, Marthi; Venter, Marietjie; Cohen, Cheryl; et al.
Abstract: Background: The association of rhinovirus (RV) detection to illness is poorly understood. Methods: We enrolled case patients hospitalized with severe respiratory illness (SRI) at 2 hospitals and outpatients with influenza-like illness (ILI) and asymptomatic individuals (controls) from 2 affiliated clinics during 2013–2015. We compared the RV prevalence among ILI and SRI cases to those of controls stratified by human immunodeficiency virus (HIV) serostatus using penalized logistic regression. The attributable fraction (AF) was calculated. Results: During 2013–2015, RV was detected in 17.4% (368/2120), 26.8% (979/3654), and 23.0% (1003/4360) of controls, ILI cases, and SRI cases, respectively. The RV AF (95% confidence interval) was statistically significant among children aged <5 years (ILI: 44.6% [30.7%–55.7%] and SRI: 50.3% [38.6%–59.9%]; P < .001) and individuals aged ≥5 years (ILI: 62.9% [54.4%–69.8%] and SRI: 51.3% [38.7%–61.3%]; P < .001) as well as among HIV-infected (ILI: 59.9% [45.8%–70.3%] and SRI: 39.8% [22.3%–53.3%]; P < .001) and HIV-uninfected (ILI: 53.6% [44.7%–61.1%] and SRI: 55.3% [45.6%–63.2%]; P < .001) individuals. Conclusions: Although RV detection was common among controls, it was also associated with a substantial proportion of clinical illness across age groups, irrespective of HIV status. Abstract : Rhinoviruses are commonly identified among asymptomatic individuals but may still be associated with a substantial proportion of mild and severe respiratory illness across age groups and among HIV-infected and HIV-uninfected individuals in South Africa.